2015
DOI: 10.1002/cm.21229
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal relationships between the cell shape and the actomyosin cortex of periodically protruding cells

Abstract: We investigate the dynamics of cell shape and analyze the actin and myosin distributions of cells exhibiting cortical density traveling waves. These waves propagate by repeated cycles of cortical compression (folding) and dilation (unfolding) that lead to periodic protrusions (oscillations) of the cell boundary. The focus of our detailed analysis is the remarkable periodicity of this phenotype, in which both the overall shape transformation and distribution of actomyosin density are repeated from cycle to cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 30 publications
(41 reference statements)
1
30
0
Order By: Relevance
“…These results suggest possible mechanisms for some observed biological phenomena and experimentally testable predictions. For example, oscillations and traveling waves in actomyosin cortex have been observed in amnioserosa cells during dorsal closure in Drosophila embryos 13 and in periodically protruding cells 34 . Even though the presented model may be too simple for a direct comparison to these experiments, our results show that a homogeneous level of activity alone is sufficient for generating such behavior.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest possible mechanisms for some observed biological phenomena and experimentally testable predictions. For example, oscillations and traveling waves in actomyosin cortex have been observed in amnioserosa cells during dorsal closure in Drosophila embryos 13 and in periodically protruding cells 34 . Even though the presented model may be too simple for a direct comparison to these experiments, our results show that a homogeneous level of activity alone is sufficient for generating such behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Actin polymerization alone is known to generate forces that are sufficient to drive protrusions at the leading edge of migrating cells (Keren et al, ; Mitchison & Cramer, , Prass, Jacobson, Mogilner, & Radmacher, ; Rottner & Stradal, ). The role of cortical actin dynamics in cell migration on flat substrates has been a subject of intense investigation (Blanchoin et al, ), and recent studies found that fluorescent signals from the plasma membrane and the F‐actin cortical cytoskeleton are highly correlated in all stages of cell protrusion and actin wave propagation (Driscoll, Losert, Jacobson, & Kapustina, ; Kapustina, Elston, & Jacobson, ). Our data showing reduction in the phosphorylated forms of FAK and paxilin suggest that L. amazonensis infection may impair the formation of adhesion signaling complexes at focal adhesions/podosomes on the plasma membrane, an effect likely to influence the dynamic changes that we observed in the cortical actin cytoskeleton (Gardel, Schneider, Aratyn‐Schaus, & Waterman, ).…”
Section: Discussionmentioning
confidence: 99%
“…The actin wave propagation speed in infected and control macrophages was measured using space/time plots (Driscoll, Sun, Guven, Fourkas, & Losert, , Driscoll et al . , ). Actin waves near the lamellipodia were cropped and resized into a single‐pixel width using ImageJ software (NIH).…”
Section: Methodsmentioning
confidence: 97%
“…Traveling membrane waves are defined as a cell membrane protrusion traveling laterally along the membrane, and are typically associated with leading edge actin polymerization33343536. We examined traveling wave formation during protrusion/retraction with our panel of LKB1 constructs (Fig.…”
Section: Resultsmentioning
confidence: 99%